Effect of waterlogging on physical and mechanical properties of Samanea saman (Jacq.) Merr. tree - Elias, -; Das, AK; Rahman, MM; Islam, MA (Bangladesh Journal of Scientific and Industrial Research, 2017)
This research intends to explore the mechanical and physical properties of waterlogged rain tree (Samanea saman). The variation of mechanical and physical wood properties grown in waterlogged and non-waterlogged area were studied. Four trees of the species were selected from two areas. Important mechanical and physical properties were examined for the wood of two types of trees Oven dry density for the wood of waterlogged tree was 420 kg/m3 whether it was 550 kg/m3 for the wood of non-waterlogged tree. The MOR of wood of waterlogged tree was 58.2 N/mm2 and wood of non-waterlogged tree produced 78.1 N/mm2. The MOE of the wood of waterlogged tree and non-waterlogged tree were 1478 and 4876 N/mm2. The physical and mechanical properties were lower for the wood of waterlogged tree. Such findings may in proper uses of the species. Bangladesh J. Sci. Ind. Res. 52(1), 49-52, 2017